The plant paradox [compact disc, unabridged] : the hidden dangers in "healthy" foods that cause disease and weight gain - Gundry, Steven R. (Tantor Audio, 2017)
Most people have heard of gluten, a protein found in wheat that causes widespread inflammation in the body. Americans spend billions of dollars on gluten-free diets in an effort to protect their health. But what if they've been missing the root of the problem? Here, renowned cardiologist Dr. Steven Gundry reveals that gluten is just one variety of a common, and highly toxic, plant-based protein called lectin.